Numerical study on the effects of installing an inducer on a pump in a turbopump. (December 2021) - Kim, Changhyun; Choi, Chang-Ho; Kim, Semi; Baek, Jehyun
In a projectile, a turbopump is widely used to pressurize oxidizer and fuel to gain high thrust instead of using high pressure tank which has a disadvantage in total weight. Pumps in a turbopump employ an inducer upstream to prevent performance degradation by increasing pressure at the impeller inlet. However, cavitation and related instabilities take place frequently, so numerous analysis have been conducted for turbopumps. In this study, the pumps with and without an inducer were numerically studied using ANSYS CFX 13.0 to analyze the effects of installing an inducer, which was rarely treated before. By comparing these two pumps, the merits and demerits of installing an inducer can be analyzed in the aspects of hydraulic/suction performances and internal flow characteristics. Also, the role of an inducer can be understood in both of non-cavitating and cavitating conditions. As a result, head rise and efficiency of the pump were degraded by installing an inducer in non-cavitating conditions. The inducer could not play a role at high flow rate, and efficiency of the inducer was steeply declined in the off-design conditions. However, suction performance of the pump was greatly improved by adopting the inducer. Head of the pump with an inducer abruptly decreased at the low cavitation numbers, while head of the pump without an inducer started to decline gradually at the high cavitation numbers. In spite of high cavitation number, severe cavitation appeared in the case without an inducer, so it can be said that installing an inducer can prevent performance deterioration from the cavitation and satisfies stable operation which is more important for pumps rather than obtaining high hydraulic performance.